Assessment of coeliac disease prevalence in patients with Down syndrome in Poland – a multi-centre study - Szaflarska-Popławska, Anna; Soroczyńska-Wrzyszcz, Anetta; Barg, Ewa; Józefczuk, Jan; Korczowski, Bartosz; Grzybowska-Chlebowczyk, Urszula; Więcek, Sabina; Cukrowska, Bożena (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : The results of studies assessing whether patients with Down syndrome have increased risk of coeliac disease are contradictory. The prevalence of coeliac disease in patients with Down syndrome is estimated at a wide range between 1% to as much as 18.6%. Aim : To assess coeliac disease prevalence in patients with Down syndrome in Poland. Material and methods : The study enrolled 301 patients with Down syndrome from six centres in Poland (Wroclaw, Sandomierz, Rzeszow, Grudziadz, Katowice, and Bydgoszcz). We measured the concentration of anti-tissue transglutaminase IgA antibodies and anti-deamidated gliadin peptide IgG antibodies in all patients. Patients with abnormal positive (> 10 U/ml) or inconclusive (7–10 U/ml) result of the serological test were offered endoscopic biopsy of the small intestine in the main centre. Results : In 31 (10.3%) patients increased concentrations of the investigated antibodies were found, including 19 (6.3%) patients with increased tTg-IgA concentration, 27 (8.97%) patients with increased concentration of DGP-IgG, and 15 (4.98%) patients with increased concentration of both types of antibodies. Endoscopic biopsy of the small intestine was planned for all 31 patients with abnormal results of at least one antibody test and for 2 patients with inconclusive results. One of them suffered from previously diagnosed and histologically confirmed coeliac disease. Biopsy was not conducted in 9 patients due to contraindications, lack of their consent, or introduction of a gluten-free diet by the parents before the examination. In a group of 23 patients who underwent endoscopic biopsy of the small intestine, in 15 patients the histopathological picture of the small intestinal mucosa was typical for coeliac disease, 2 patients were diagnosed with lesions of grade 1 according to the classification by Marsh-Oberhuber, 1 patient was diagnosed with focal shortening of villi and hypertrophy of the crypts with no intraepithelial lymphocytosis (remains under gastrological observation), 2 patients were diagnosed with mucosal inflammation of the duodenum, and 3 patients were found to have a normal histopathological picture of the small intestine. Analysis of the data included in the questionnaires of all patients showed no statistically significant differences in the body height, body mass index, prevalence of abdominal pain, diarrhoea, constipations, recurrent stomatitis, enamel hypoplasia, thyroid diseases, or hypertransaminasaemia between the groups of patients with normal and abnormal serological test results. Significantly higher prevalence of abdominal flatulence (p < 0.05) and epilepsy (p < 0.05) was found in the group of patients whose serological test results were negative. Conclusions : Patients with Down syndrome are a high-risk group for coeliac disease in the Polish population, with an estimated prevalence of at least 5.4%. Serological tools based on tTG-IgA and DGP-IgG tests are useful for the diagnosis of coeliac disease in Down syndrome patients. tTG-IgA test may be superior to DGP-IgG test in patients with normal total IgA level. Tests for coeliac disease should be carried out in all Polish patients with Down syndrome, regardless of the clinical picture.